2022
DOI: 10.1097/tp.0000000000004270
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Chronic Lung Allograft Dysfunction: Ready for Prime Time?

Abstract: Chronic lung allograft dysfunction (CLAD) remains a major hurdle impairing lung transplant outcome. Parallel to the better clinical identification and characterization of CLAD and CLAD phenotypes, there is an increasing urge to find adequate biomarkers that could assist in the earlier detection and differential diagnosis of CLAD phenotypes, as well as disease prognostication. The current status and state-of-the-art of biomarker research in CLAD will be discussed with a particular focus on radiological biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Transbronchial lung biopsies are typically performed to assess for evidence of acute cellular or antibody mediated rejection as routine surveillance or in patients with worsening lung function. Identifying CLAD with transbronchial biopsies has a low yield, but findings such as organizing pneumonia and bronchial eosinophilia can suggest CLAD in the appropriate clinical context [33].…”
Section: Strategies To Prevent Cladmentioning
confidence: 99%
See 1 more Smart Citation
“…Transbronchial lung biopsies are typically performed to assess for evidence of acute cellular or antibody mediated rejection as routine surveillance or in patients with worsening lung function. Identifying CLAD with transbronchial biopsies has a low yield, but findings such as organizing pneumonia and bronchial eosinophilia can suggest CLAD in the appropriate clinical context [33].…”
Section: Strategies To Prevent Cladmentioning
confidence: 99%
“…In addition, circulating donor specific antibodies have been linked to the developing of acute rejection and CLAD. Persistence of high levels of donor specific antibodies has been associated with the RAS phenotype in particular [33]. Plasma levels of donor-derived cell free DNA (dd-cfDNA) from the lung allograft increase during episodes of rejection, and thresholds with high sensitivity and negative predictive value have been established to detect rejection, even in asymptomatic patients [28].…”
Section: Strategies To Prevent Cladmentioning
confidence: 99%
“…Numerous publications have analysed different immune cell profiles and their connection to lung allograft dysfunction [109][110][111]. BROSSEAU et al [110] demonstrated that LTRs with a frequency of CD9 + B-cells below 6.6% in peripheral blood had a significantly higher incidence of BOS.…”
Section: Lymphocyte Subset Assaysmentioning
confidence: 99%
“…Peripheral blood is an easily accessible biological sample frequently used in the search for the "ideal biomarker". Multiple studies have tried to identify biomarkers of rejection in peripheral blood for the early diagnosis of ACR and CLAD [15][16] . In this regard, we can highlight, amongst others, the determination of several cytokines and chemokines, KL6, exosomes, or donor-derived cell-free DNA.…”
Section: Biomarkers In Peripheral Bloodmentioning
confidence: 99%